Time-Induced Progressive Alteration of Kir Current in Cerebral Smooth Muscle Cells of Stroke-Prone Spontaneously Hypertensive Rats - Michèle Bastide; Thavarak Ouk; Olivier Pétrault; Régis Bordet (International Journal of Hypertension)
We investigated the involvement of potassium inward rectifier current (Kir) impairment in smooth muscle cells of cerebral arteries under the condition of increased susceptibility of stroke, in spontaneously hypertensive stroke-prone (SHRsp) rats compared to spontaneously hypertensive (SHR) ones as well as to controls (WKY). Kir current was studied with whole-cell patch-clamp techniques on freshly isolated single smooth muscle cells (SMC) of middle cerebral artery (MCA) from SHRsp, SHR, and WKY male rats (are range 12–32 weeks). A significant and progressive Kir current density reduction was observed on SMC of SHRsp rats from the 22nd week of age on, as opposed to the Kir current density stability observed over the same time in the SMC of WKY and SHR rats. The Kir density alteration was correlated to the age of the SHRsp animals. These results suggest that in the cerebral vascular smooth muscle cells of SHRsp rats, there is a progressive Kir channel impairment, leading to a reduction of Kir current density. This impairment may underpin a lack of vasodilation of the MCA and be implicated in the stroke-proneness observed on SHRsp animals.